Measurement of apparent diffusion coefficient in discrimination of benign and malignant axillary lymph nodes - Yılmaz, Ebru (Pol J Radiol, 2019)
PURPOSE: We aimed to determine the contribution of the apparent diffusion coefficient (ADC) value in the detection of axillary lymph node metastasis. MATERIAL AND METHODS: Breast magnetic resonance of 58 patients, performed in the radiology clinic of our hospital between 2015 and 2017 were examined retrospectively, and 43 lymph nodes in 43 patients were included in the study. They were evaluated morphologically on T1W and T2W sequences, and the lymph nodes showing rounded shape, focal or diffuse cortical thickness of more than 3 mm, and partial or total effacement of fatty hilum were included in the study. Subsequently, their ADC values were measured. RESULTS: There were 43 lymph nodes, 20 of which were malignant and 23 of which were benign. While the mean ADC value of malignant axillary lymph nodes was 0.749 10(–3) mm(2)/s (0.48-1.342), it was 0.982 10(–3) mm(2)/s (0.552-1.986) for benign lymph nodes. When the ADC cut-off value was taken as ≤ 0.753 × 10(–3) mm(2)/s, its discrimination power between benign and malignant axillary lymph nodes was as follows: sensitivity – 60%; specificity – 91.3%; accuracy – 76.7%; positive predictive value – 85.7%; and negative predictive value – 72.4%. CONCLUSIONS: There was no significant difference between mean ADC value of 12 lymphadenopathies (LAP) associated with inflammatory breast diseases (granulomatous mastitis and acute suppurative mastitis) and mean ADC value of metastatic lymph nodes. However, the ADC value of lymph nodes showing thickened cortex due to systemic inflammatory diseases was over 1, and there was a statistically significant difference when compared with metastatic lymph nodes.